Surgically Induced Corneal Astigmatism in Conventional 20-Gauge Versus Trans-Conjunctival Sutureless 23-Gauge Vitrectomy - Chaudry Nasir Ahmad, Zoya Raza, Syed Raza Ali Shah,Tehseen Mehmood Mahju , Qasim Lateef Chaudry, Asad Aslam Khan (Pakistan Journal of Ophthalmology, 2018)
Purpose: The purpose of the study was to evaluate and compare the effects of 23G (gauge) tran-sconjunctival pars plana vitrectomy (PPV) with conventional 20G PPV in inducing corneal astigmatism. Material and Methods: This was comparative, consecutive interventional study done at Institute of Ophthalmology Mayo Hospital Lahore from January 2011 till June 2011. 40 patients were selected and divided into two equal groups. Group I patients underwent 23G trans-conjunctival PPV while patients in group II were operated by conventional 20G PPV. Evaluation was done on 1st postoperative day, the 1st follow-up visit (after one week), 2nd follow up visit (after one month), 3rd follow-up visit (2 months post-op) and on fourth follow-up visit (after 3 months). On each visit keratometry (Huvitz Keratometer) along with anterior segment examination, posterior segment examination and intraocular pressure measurement were performed. Results: There were total of forty patients divided into two equal groups, 22 were males and 18 females. Group-I was operated by trans-conjunctival 23G PPV whereas the group II underwent conventional 20G PPV. The surgically induced corneal astigmatism was lower at one week postoperatively in the 23G group (P = .006) compared with the 20G group (P = .001). One month postoperatively, the surgically-induced corneal astigmatism was still lower in the 23G group (P = 01). Conclusion: 23G PPV induces much less surgically induced corneal astigmatism in comparison to 20G PPV.